Phthalocyanines prepared from 4-chloro-/4-hexylthio-5-(4-phenyloxyacetic acid)phthalonitriles and functionalization of the related phthalocyanines with hydroxymethylferrocene - (:unkn) unknown (ELSEVIER SCIENCE SA, 2010)
The phthalonitrile derivative chosen for the synthesis of substituted phthalocyanines [M: 2H, Zn(II), Co(II)] with four chloro and four phenyloxyacetic acid substituents on the periphery is 4-chloro-5-(4-phenyloxyacetic acid) phthalonitrile. The sodium salt of carboxyl substituted zinc phthalocyanine is good soluble in water. Further reactions of zinc and cobalt phthalocyanines bearing phenyloxyacetic acid with thionylchloride gave the corresponding acylchlorides. This functional group reacted with hydroxymethylferrocene in dry DMF to obtain ferrocenyl substituted phthalocyanines. Also chloro substituent in new phthalonitrile was substituted with hexylsulfanyl substituent and its cyclotetramerization in the presence of Zn(AcO)(2)center dot 2H(2)O and 2-(dimethylamino) ethanol resulted with zinc phthalocyanine. The compounds have been characterized by elemental analysis, MALDI-TOF mass, FT-IR, H-1 NMR, UV-Vis and fluorescence data. Aggregations properties of phthalocyanines were investigated at different concentrations in tetrahydrofuran, dimethylformamide, dimethylsulfoxide, water, and water/ethanol mixture. Also fluorescence spectral properties are reported. (C) 2009 Elsevier B. V. All rights reserved.
Keywords: Water-soluble zinc phthalocyanine; Aggregation; Hydroxymethylferrocene; Fluorescence; SULFONATED PHTHALOCYANINES; FERROCENE; FLUORESCENCE; COMPLEXES; ANNELIDES; OXIDATION; MOIETIES